1985
DOI: 10.3109/17453678508994338
|View full text |Cite
|
Sign up to set email alerts
|

Occupational capacity after hip replacement

Abstract: Working capacity and dependence on the social welfare system were analyzed in 387 patients 5 years after hip replacement. Significant pre-operative factors were age, etiology of the hip disease and walking ability, and at the follow-up age, walking ability, pain and subjective experience of satisfaction with the operation. Among patients working pre-operatively, 92 per cent kept on working, and 70 per cent of patients on sick-leave went back to work. Only 9 per cent of patients working or sick-listed pre-opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…Johnsson and Persson 5 went as far as to discover a positive association between the duration of preoperative and postoperative sick leaves and demonstrated that a reduction of sick leave to 6 months or less meant a productive gain to society. Our results parallel this study and the study of Jensen et al 6 on occupational capacity after hip replacement. In their study, of 99 patients under 60 years, the majority of those working pre-operatively continued to work after hip replacement and two-thirds of sick-listed patients returned to work.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Johnsson and Persson 5 went as far as to discover a positive association between the duration of preoperative and postoperative sick leaves and demonstrated that a reduction of sick leave to 6 months or less meant a productive gain to society. Our results parallel this study and the study of Jensen et al 6 on occupational capacity after hip replacement. In their study, of 99 patients under 60 years, the majority of those working pre-operatively continued to work after hip replacement and two-thirds of sick-listed patients returned to work.…”
Section: Discussionsupporting
confidence: 93%
“…8 Only a few studies have been undertaken looking specifically at the effect of THR on the ability of patients of working age to continue or resume active employment. [4][5][6][7] This is important because the cost of sick leave in patients awaiting total hip replacement is substantial. 9 In our study, all but one of those who were working preoperatively remained in work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis for returning to work after hip and back surgery is poor for patients with a preoperative disability pension (Jensen et al 1985, Johnsson and Persson 1986, Jonsson and Stromqvist 1994, and we found the same after knee replacement. This might be explained by progressive impairment in work motivation induced by the disability pension-an explanation in accordance with our results in the NHP part of the investigation, where patients on partial or complete disability pension showed impairment in the psychological categories but not in the physical capacity categories.…”
Section: Discussionsupporting
confidence: 70%
“…To diminish the risk of mechanical loosening of the prosthesis, the patients should avoid going back to heavy work. The prognosis of returning to work after surgery is poor for preoperatively retired patients (Wadensjo 1980, Kromann-Andersen & Jorgensen 1980, Jensen et al 1985.…”
Section: Discussionmentioning
confidence: 99%